Modeling the Temporal Variations in the Output of Large Solar PV Power Plants. (September 2016) - Femin, V.; Petra, M.I.; Mathew, S.; Hazra, J.; Ismail, H.
Abstract: With the rapid increase in the cumulative installations around the world, solar PV technology has started playing a major role in the global clean energy scenario. One of the major challenges for the large scale integration of solar energy with the power grids is its intermittent nature. In this paper, temporal variations in the power output of six different solar PV technologies are quantified and modeled. The solar cells considered are single crystalline, poly crystalline, micro crystalline amorphous silicon, copper Indium Selenium (CIS) and hetero-junction with intrinsic thin layer (HIT). Three years of performance data from a 1.2 MW experimental solar PV farm in Brunei Darussalam were used for the modeling. It was found that the variations in the PV output follow the Cauchy's probability distribution. Ramping down behaviour of the solar panel was critically analyzed and expected ramp downs at 95% confidence level are presented. HIT modules showed the highest ramp rate among the panels, whereas CIS showed the lowest fluctuations.